Management of Malignant Otitis Externa with Hyperbaric Oxygen Therapy: A Case Series of 20 Patients - Abdulhameed Al Siyabi; Badriya Al Farsi; Asma Al-Shidhani; Zainb Al Hinai; Yousuf Al Balushi; Hassan Al Qartoobi (Oman Medical Journal, 2023)
Malignant otitis externa (MOE) is an aggressive infection of the external auditory canal that primarily affects diabetic patients. Some literature supports the effectiveness of hyperbaric oxygen therapy (HBOT) as a treatment modality for MOE. A case series was conducted of all patients diagnosed with MOE and treated with HBOT at the Said Bin Sultan Naval Base Polyclinic in Oman between January 2014 and December 2019. A total of 20 patients were included in the study. All participants presented with persistent ear discharge, 95.0% with otalgia, and 75.0% with granulation in the external auditory canal. Moreover, 100% showed abnormally high levels of inflammatory markers and abnormal computed tomography findings. The patients underwent an average of 29.0±8.9 HBOT sessions. Overall, 19 (95.0%) patients were considered cured by the end of the treatment. The use of HBOT in the management of MOE appears promising and may cure MOE.